Analysis of Innovation based on Technometric Model to Predict Technology Life Cycle in Indonesian SME - Ganesha Putri, Debby Cintia; Handayani, Wahyu Sri; Sulistyawan, Vera N; Rumanti, Augustina Asih; Hadisurya, Vania (International Journal of Innovation in Enterprise System, 2017)
Forecasting technology is one way that can be used to predict product life cycle. Product life cycle is very important to know, especially by organizations, that are in small medium level, like SME. This research will be conducted in SME Surya Usaha Mandiri, Daerah Istimewa Yogyakarta.Forecasting product life cycle that has been done, will direct this research toward the stage of product development. Stages of development of the products are a necessary stage for an organization, especially in SME, to innovate the product. The purpose of this research is to propose the development of products, such as the stages of innovation that can be done in SME Surya Usaha Mandiri, forecasting conducted based on life cycle assessment of products and technology components using technometric model. The results of this research are proposed innovation based forecasting and product life cycle assessment in SME Surya Usaha Mandiri using technometric model. Keywords - product life cycle, innovation, technometric model, SME